2021
DOI: 10.36909/jer.v9i3b.9733
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effect of different aggregate types on concrete properties with thin section and nondestructive methods

Abstract: Concrete is the most important material in construction industry. Aggregate is one of the most important components of concrete, which consists of many different components. In this study, concrete of constant water/cement ratio was produced by using different types of aggregates, and the effect of aggregate on concrete properties was investigated. After determining the physical properties of the aggregates, the textural properties of the aggregates were investigated with the help of image analysis. Standard w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It has a wide range of applications in the aerospace and wind turbine industries, among other areas [ 5 , 29 , 90 , 91 ]. The shearography techniques present several advantages over traditional NDT techniques, including (1) being capable of testing large area on the structure (up to 1 m 2 per minute [ 92 ]), (2) providing contactless techniques, (3) being relatively insensitive to environmental variations effects, and (4) performing well on honeycomb materials [ 93 ].…”
Section: Shm Of Composite Structuresmentioning
confidence: 99%
“…It has a wide range of applications in the aerospace and wind turbine industries, among other areas [ 5 , 29 , 90 , 91 ]. The shearography techniques present several advantages over traditional NDT techniques, including (1) being capable of testing large area on the structure (up to 1 m 2 per minute [ 92 ]), (2) providing contactless techniques, (3) being relatively insensitive to environmental variations effects, and (4) performing well on honeycomb materials [ 93 ].…”
Section: Shm Of Composite Structuresmentioning
confidence: 99%
“…For instance, the use of calcareous sand in concrete reduces workability and increases long-term strength compared to concrete based on siliceous sand [17,18]. Consequently, the compressive strength and modulus of elasticity of concrete with calcareous aggregates are slightly higher than those found in the case of quartz aggregates [19][20][21]. Furthermore, Ortiz et al [22] and Alhozaimy [23] demonstrated that the workability of mortar decreases depending on the temperature of the sand.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of the micromechanics of asphalt concrete, the size, shape, distribution, and interaction of particles directly affect the mechanical properties of asphalt mixtures, such as strength. The microstructure of concrete directly affects its macroscopic mechanical properties [3][4][5][6][7][8][9][10][11]. A large number of domestic and foreign scholars have studied the mechanism of the influence of mixture structure on its performance at the microscale using two main methods: analytical and numerical [12,13].…”
Section: Introductionmentioning
confidence: 99%